Analisis dan Perancangan Sistem Informasi Perpustakaan IBI Kwik Kian Gie - Sigit Birowo (Jurnal Informatika dan Bisnis, 2013)
The development is important given the current library role in education is very large and interactdirectly with users and operators. In the higher education institutions, the library is one of thealternatives in the search for the required inforrnasi lecturer, rnahasiswa and employees to increaseknowledge.all that without supported by an integrated administrative services will be imbalance betweeninputs, outputs and processes. Until now it was all done with such manual records of booksborrowed and return of books, noting that student lists delinquent fines or books, recording a list ofnew books, recording the entire subscription magazines, newspapers, journals and other libraryrelatedadministration. If there is an error in the manual process it takes a relatively long time.Based on the problems that exist today it needs to make the library administration system with theaim, among others: increased work efficiency, service can be maximized, Issuing reports requiredto be on time, controlling the borrower of books, library books and reports evaluating bills, overduefines